Effects of Ethephon and Fertilization on Latex Physiology and Rubber Yield in GT1, BPM 24, PB260 and IRR112 Clones - Ardika, Risal; Sanchez, Pearl B. (Journal of Tropical Crop Science, 2026)
This study was conducted to evaluate the effects of ethephon stimulation and fertilization on latex production and physiological latex in different clones. This study was conducted in the experimental field of the Indonesian Rubber Research Institute in South Sumatra. The experiment was laid out in a randomized complete block design with three replications. The main block is the rubber clones, and the subblocks are fertilization rate and ethephon stimulation. The rubber clones for this research were GT 1, BPM 24, PB 260, and IRR 112. The different fertilization rates used in the experiment were control (no fertilizer), 50% recommended rate (50 RR), 100% recommended rate (100 RR), and 150% recommended rate (150 RR). Ethephon stimulation was applied every two months during the observation period with a rate of S/2 d3 ET2.5% 6/y. The observed parameters included: latex yield, physiological latex (sucrose, inorganic phosphorus, and thiol), and tapping panel dryness. Results showed that rubber yields, such as latex production and dry rubber content, increased by 10%–16% with fertilization and ethephon stimulation. Latex characteristics, including thiol, inorganic phosphate, and sucrose, remained within their optimal ranges, with thiol levels increasing from 0.11 to 0.29 mM, inorganic phosphate from 7.29 to 1.58 mM, and sucrose from 0.42 to 7.12 mM upon fertilization.